Implementation Of Natural Language-Based Chatbot Processing On The LPPMB Web at UNIQHBA - Muhammad Hamzani Wahid (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2026)
The development of artificial intelligence technology, particularly Natural Language Processing (NLP), has provided significant opportunities to improve the quality of information services in various sectors, including higher education. In the new student admissions (PMB) process, providing fast, accurate, and easily accessible information is a crucial requirement for prospective students. However, limited customer service often leads to delays in information delivery. This study aims to implement an NLP-based chatbot on the LPPMB website of Qamarul Huda Badaruddin University (UNIQHBA) to improve the efficiency of PMB information services. The research method is descriptive and quantitative, and the system development uses the Agile method. Data were collected through observation, interviews, and documentation. The chatbot system was developed by utilising the n8n platform for workflow automation and an NLP-based AI model for natural language processing. System testing was carried out through chatbot response testing and measuring user satisfaction using the Customer Satisfaction Score (CSAT). The results showed that the chatbot provided real-time, relevant responses to user questions about PMB. In addition, the user satisfaction rate reached 85%, indicating that the system effectively met information needs. Thus, the implementation of an NLP-based chatbot has been proven to improve the quality of information services and reduce the workload of customer service personnel. This research is expected to serve as a reference for developing chatbot systems in educational settings.